Relationship between the mean of 24-h venous blood glucose and in-hospital mortality among patients with subarachnoid hemorrhage: A matched cohort study - Wang, Jun-Hong; Li, Hua; Yang, Hong-Kuan; Chen, Ru-Dong; Yu, Jia-Sheng (Frontiers in Neurology, 2022)
Objective The aim of this study was to explore the correlation between the mean of 24-h venous blood glucose (BG) and in-hospital mortality and all-cause mortality (ACM) in patients with subarachnoid hemorrhage (SAH). Methods Detailed clinical information was acquired from the Medical Information Mart for Intensive IV (MIMIC-IV) database. The best cutoff value of mean BG was calculated using the X-tile program. Univariate and multivariate logistic regressive analyses were utilized to analyze the prognosis significance of mean BG, and survival curves were drawn using the Kaplan-Meier (K-M) approach. To improve the reliability of results and balance the impact of underlying confounders, the 1:1 propensity score matching (PSM) approach was utilized. Results An overall of 1,230 subjects were selected herein. The optimal cutoff value of the mean BG for in-hospital mortality was 152.25. In addition, 367 pairs of score-matched subjects were acquired after PSM analysis, and nearly all variables' differences were balanced. K-M analysis showed that patients with mean BG ≥ 152.25 mg/dl had significantly higher in-hospital, 3-month, and 6-month mortalities compared with patients with mean BG < 152.25 mg/dl (p < 0.001). The multivariable logistic regressive analyses revealed that patients with mean BG ≥ 152.25 mg/dl had significantly increased in-hospital mortality compared with patients with mean BG < 152.25 mg/dl after the adjustment for possible confounders (OR = 1.994, 95% CI: 1.321–3.012, p = 0.001). Similar outcomes were discovered in the PSM cohort. Conclusion Our data suggested that mean BG was related to ACM of patients with SAH. More studies are needed to further analyze the role of the mean of 24-h venous BG in patients with SAH.